THE CORRELATION BETWEEN THE USE OF SOCIAL MEDIA AND VOCABULARY MASTERY OF THE FIFTH SEMESTER STUDENTS OF THE ENGLISH STUDY PROGRAM UNIVERSITAS RIAU - Karin Noviana; Novitri Novitri; Syarfi Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The aim of this research is to find out whether or not there is significant correlation between social media usage and English vocabulary mastery of the fifth-semester students of the English Study Program Universitas Riau. By applying the quantitative method, this research used a population with the total 112 students of the fifth semester, while the samples were 76 students, who were selected using a cluster random sampling technique. The research isntruments are a Questionnaire and a Test. The questionnaire is to measure social media usage (Safitri, 2021; Sivagnanam and Yunus, 2020), and the vocabulary test is to measure the vocabulary mastery of the students adapted from TOEFL book (Riau University Language Center, 2014) and TOEFL book by (Kardimin, 2008). The researcher used IBM SPSS Statistics 25 to analyze the data. The results of the data analysis showed that the average student's use of social media is 92.3, which is considered to be at a